El grupo epidanthus, subgrupo selaginella de epidendrum - Hágsater, Eric; Santiago Ayala, Elizabeth (Lankesteriana: International Journal on Orchidology, 2014)
The revision of a large number of herbarium specimens determined as Epidendrum selaginella Schltr. and which had evident foliar differences compared to the type served to prepare a detailed description of this widely distributed species in Costa Rica and Panama, and an analysis of the floral segments led to the recognition of two new species closely allied to Epidendrum selaginella, and confused with that Central American species: Epidendrum astroselaginella, and Epidendrum stenoselaginella. An illustrated key is provided.